2002
DOI: 10.1046/j.1365-2672.2002.01698.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l-malic and citric acids metabolism on the essential amino acid requirements for Oenococcus oeni growth

Abstract: Aims: The purpose of this work was to study the effect of L-malic and ⁄ or citric acids on Oenococcus oeni m growth in deficient nutritional conditions, and their roles as possible biosynthetic precursors of the essential amino acids. Methods and Results: Bacterial cultures were performed in synthetic media. Bacterial growth rate was reduced or annulled when one amino acid was omitted from basal medium, especially for members of aspartate family, except lysine. The organic acids increased or restored the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
5
26
0
Order By: Relevance
“…The results of fermentation balances demonstrated that the D-lactic acid formed from sugars metabolism by inoculated microorganism was lower than expected theoretical value indicating that sugars metabolism could be involved in biosynthesis reactions. Saguir and Manca de Nadra (2002) reported in Oenococcus oeni that glucose metabolism was involved in the cysteine biosynthesis. In contrast, the amount of acetic acid + ethanol recovered from glucose + fructose was 65% higher than the expected theoretical value.…”
Section: Discussionmentioning
confidence: 99%
“…The results of fermentation balances demonstrated that the D-lactic acid formed from sugars metabolism by inoculated microorganism was lower than expected theoretical value indicating that sugars metabolism could be involved in biosynthesis reactions. Saguir and Manca de Nadra (2002) reported in Oenococcus oeni that glucose metabolism was involved in the cysteine biosynthesis. In contrast, the amount of acetic acid + ethanol recovered from glucose + fructose was 65% higher than the expected theoretical value.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is often difficult to trigger and accomplish because of the individual or synergistic antibacterial activity of several physical chemical wine parameters and yeast inhibitory metabolites. Some of these factors have been intensively investigated such as low pH (Britz and Tracey, 1990;Vaillant et al, 1995), inadequate temperature (Britz and Tracey, 1990), nutrient depletion (Patynowski et al, 2002;Remize et al, 2006;Saguir and Manca de Nadra, 2002;Terrade and Mira de Orduna, 2009), endogenous and exogenous SO 2 (Carreté et al, 2002;Henick-Kling and Park, 1994;Larsen et al, 2003;Osborne and Edwards, 2006), phenolic compounds (Reguant et al, 2000), high ethanol content (Britz and Tracey, 1990;Vaillant et al, 1995) and medium chain fatty acids (Capucho and San Romao, 1994;Edwards and Beelman, 1987;Lonvaud Funel et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of growth of these bacteria is dependent on their ability to utilize the substrates available in the medium. LAB generally have complex nutritional requirements for growth especially with regard to nitrogen sources (Amoroso et al 1993;Elli et al 1999;Saguir and Manca de Nadra 2002;Hébert et al 2004). Saguir and Manca de Nadra (2007) demonstrated that Lact.…”
Section: Introductionmentioning
confidence: 99%